(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
An alternative of crop adaptation to climate change may be achieved by extension in new ecosystems. In this circumstance, stimulation of growth hormones should be advocated. Therefore, a fertilizer trial of wheat (Triticum durumdesf) was set in rainfed condition of the south of Côte d’Ivoire. The experiment design was a randomized complete bloc design with three replications including seven pots as treatments. A rate of 200 kgha-1 as NPK (15, 22, 22) basal fertilizer was applied. The rates of 50 kgha-1 as magnesium sulfite and 10 kgha-1 of zinc sulfite were used for the treatments NPKMg, NPKZn, NPKMgZn, Mg and Zn. A rate of 35 kgha-1 was also applied as urea at tillering and bosting stages respectively. The results showed highest grain yield in a range of 3.47 tha-1 for the treatment NPK. A negative impact of cations on photoperiod and a depressing effect of low rate of K was deemed responsible of low tillering and the limited plant high. Presuming effects of Zn and Mg were only limited to the reproductive stage without affecting the grain yield because of low development of the rhizosphere. There is chance to increase the grain yield of 3.47 tha-1 recorded by for the treatment NPK when increasing the rate of K for improving wheat production in the forest zone of south Côte d’Ivoire.